Utilizando chaves ópticas para controle de qualidade de serviços em redes inteligentes - Bressam, Wagner Caldas (2016)
Smart grid networks provide services with the potential to increase energy efficiency and the quality of life of society, but have strict requirements regarding response time, reliability, scalability and QoS. The optical switches are fiber optic switching devices commonly used for physical route changing. In this study, it is suggested to use these devices to actively rearrange a network in order to reduce the communication latency, to meet the communications requirements of smart grid services. The characteristics of known routing protocols have been studied and the Dijkstra algorithm has been applied at the creation of four heuristics that aim to optimize the maximum paths in networks with optical switches. The simulations show that the heuristics reduce the maximum number of hops in the paths, leading to reductions in latency. It is suggested the continuation of this study improving the heuristics with other optimization engines and different metrics, such as reducing traffic congestion and energy.